Alexandria's hinterland : archaeology of the western Nile Delta, Egypt - Kenawi, Mohamed, (Archaeopress archaeology., 2014)
This volume contains detailed information about 63 sites and shows, amongst other things, that the viticulture of the western delta was significant in Ptolemaic and Roman periods, as well as a network of interlocking sites, which connected with the rest of Egypt, Alexandria, North Africa and the Eastern Mediterranean and Aegean.